2007
DOI: 10.1177/0002716207303590
|View full text |Cite
|
Sign up to set email alerts
|

Building Ventures through Civic Capitalism

Abstract: An exploratory study of urban entrepreneurs participating in a technical assistance program finds that they focus on the bottom line and often have an explicit wish to improve their community. This integrated combination of economic and social values, a kind of civic-minded capitalism, guides their positioning for growth and yields a business that can best be called a “civic enterprise.” A descriptive analysis of qualitative and quantitative research yields propositions for future research on these hybrid busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A recent exploratory study of inner city and minority entrepreneurs revealed that minority entrepreneurs were more likely to be running their first venture (as compared to having started numerous businesses), were more deeply involved in their communities, and were motivated by both social and economic goals. Interviews with entrepreneurs conducted as a part of this study showed that differences in motivations influenced how business owners positioned their firms for growth (Brush et al. 2007).…”
Section: Theoretical Perspectives and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent exploratory study of inner city and minority entrepreneurs revealed that minority entrepreneurs were more likely to be running their first venture (as compared to having started numerous businesses), were more deeply involved in their communities, and were motivated by both social and economic goals. Interviews with entrepreneurs conducted as a part of this study showed that differences in motivations influenced how business owners positioned their firms for growth (Brush et al. 2007).…”
Section: Theoretical Perspectives and Hypothesis Developmentmentioning
confidence: 99%
“…Academic research on entrepreneurship and growth in African American firms has considered a wide variety of topics, including the role of public policy and government procurement in encouraging growth (Rasheed 2004; Bates 2003), access to financial capital (Fairlie and Robb 2008; Coleman 2005; Lash 2005), the role of community incubators in fostering entrepreneurship (Greene and Butler 2004), and the ways minority businesses position for growth by improving management, capital access and market expansion (Brush et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies show that minority entrepreneurs have some demographic characteristics that are different from those of non-minority entrepreneurs (Bewaji et al, 2015). Specifically, minority entrepreneurs are often born in low-or middle-class families, and many are young (below the age of 30), possess college degrees, and are motivated by both social and economic goals (Gomolka, 1977;Hisrich and Brush, 1986;Brush et al, 2007). Furthermore, ethnic minority groups have higher rates of self-employment and business ownership (Bates, 2000;Fairlie, 2004a).…”
Section: Literature Reviewmentioning
confidence: 99%